Intensitas dan Sosialitas Keberagaman di Lingkungan Kerja - Yusuf Siswantara; Thomas Lingga; Willfridus Demetrius Siga (Jurnal Sosial Humaniora, 2021)
Research "intensity and sociality of diversity in the environment orwork unit", aims to find indications of work effectiveness and thevalues of diversity in a pluralistic work environment on workoptimization and productivity. This study uses a quantitative approachwith a questionnaire as a random sampling instrument. The number ofdata population is 39 respondents. The correlation of the intensity ofdiversity values and work practices in a pluralistic environment is themain aspect that supports work effectiveness both internally andexternally. Positive influence supports each person to feel safe,comfortable and have very good relationships. Based on the results ofthe analysis, this study shows that there is a strong and positivecorrelation between performance and tolerance values in a pluralisticenvironment with a positive percentage of 93% and 0.7% valuedeviation that does not support the correlation of the two variables.